International Editorial Board of vol. 27 No. 1 (2024): Journal Scientific and Applied Research: International Editorial Board of vol. 27 No. 1 (2024): Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
International Editorial Board of vol. 27 No. 1 (2024): Journal Scientific and Applied Research